To find the equivalent expression for \((6x + 8) / 2\), you can simplify it by dividing both terms in the numerator by 2:
\[ \frac{6x + 8}{2} = \frac{6x}{2} + \frac{8}{2} = 3x + 4 \]
So, the equivalent expression is:
B. \(3x + 4\)
A. 12x+16
B.3x+4
C.3x+4/2
D.12x+16/2
1 answer
To find the equivalent expression for \((6x + 8) / 2\), you can simplify it by dividing both terms in the numerator by 2:
\[ \frac{6x + 8}{2} = \frac{6x}{2} + \frac{8}{2} = 3x + 4 \]
So, the equivalent expression is:
B. \(3x + 4\)